Fragments of the key flowering gene GIGANTEA are associated with helitron-type sequences in the Pooideae grass Lolium perenne - Langdon Tim; Thomas Ann; Huang Lin; Farrar Kerrie; King Julie; Armstead Ian (BMC Plant Biology, 2009)
Abstract Background Helitrons are a class of transposable elements which have been identified in a number of species of plants, animals and fungi. They are unique in their proposed rolling-circle mode of replication, have a highly variable copy-number and have been implicated in the restructuring of coding sequences both by their insertion into existing genes and by their incorporation of transcriptionally competent gene fragments. Helitron discovery depends on identifying associated DNA signature sequences and comprehensive evaluation of helitron contribution to a particular genome requires detailed computational analysis of whole genome sequence. Therefore, the role which helitrons have played in modelling non-model plant genomes is largely unknown. Results Cloning of the flowering gene GIGANTEA (GI) from a BAC library of the Pooideae grass Lolium perenne (perennial ryegrass) identified the target gene and several GI pseudogene fragments spanning the first five exons. Analysis of genomic sequence 5' and 3' of one these GI fragments revealed motifs consistent with helitron-type transposon insertion, specifically a putative 5'-A↓T-3' insertion site containing 5'-TC and CTAG-3' borders with a sub-terminal 16 bp hairpin. Screening of a BAC library of the closely related grass species Festuca pratensis (meadow fescue) indicated similar helitron-associated GI fragments present in this genome, as well as non-helitron associated GI fragments derived from the same region of GI. In order to investigate the possible extent of ancestral helitron-activity in L. perenne, a methylation-filtered GeneThresher® genomic library developed from this species was screened for potential helitron 3' hairpin sequences associated with a 3'-CTRR motif. This identified 7 potential helitron hairpin-types present between at least 9 and 51 times within the L. perenne methylation-filtered library. Conclusion This represents evidence for a possible ancestral role for helitrons in modelling the genomes of Lolium and related species.